The structural and comparative analysis of intravitreal dexamethasone implant (Ozurdex) and anti‐VEGF injection in branched retinal vein occlusion patients by optical coherence tomography angiography images quantitation - Park, JinHeung (Acta ophthalmologica (Oxford, England), 2021)
Purpose To evaluate and compare the structural changes of retinal vasculature after intravitreal dexamethasone implant (Ozurdex) and anti‐vascular endothelial growth factor (anti‐VEGF) injection in branched retinal vein occlusion (BRVO) patients by optical coherence tomography angiography (OCTA) images quantitation. Methods We retrospectively analyzed thirty‐nine patients with unilateral BRVO. Subjects were divided into two groups according to treatment agent, Ozurdex (n = 18) and anti‐VEGF (n = 21). Swept Source (SS) OCT and OCTA were performed, and images were analyzed quantitatively by using ImageJ software. Intravitreal implant and injections were performed following a pro re nata (PRN) regimen. Anti‐VEGF agent was chosen between bevacizumab, ranibizumab and aflibercept. Results In independent two‐sample t‐test, the vessel reperfusion was more significant in intravitreal Ozurdex implant group than anti‐VEGF injection group in choriocapillaris slab of angiography mode (p = 0.013). Positive change of particles number was more prominent in intravitreal anti‐VEGF injection group than intravitreal Ozurdex implant group in outer retina slab of En‐face mode (p = 0.039). ETDRS density map (p = 0.632) and other angiography slabs; superficial (p = 0.200), deep (p = 0.199) and outer retina (p = 0.210) showed no significant difference in two treatment groups. Conclusions Quantitative analysis of OCTA images using ImageJ software showed that intravitreal Ozurdex implant seems to be better treatment than anti‐VAGF injection for BRVO in the aspect of retinal vascular reperfusion.